BACTERIAL MER GENES ARE POTENTIAL GENETIC MATERIAL FOR BIOREMEDIATION ON MERCURY POLUTION - Suwastika, I Nengah (Univ. Tadulako, 2013)
Remediation over mercury-contaminated areas become major concern and needs to be solved. Recently, various parts of ecosystem were contaminated because of increase of mercury emission into environment. Methyl-mercury is the most toxic form, which commonly found in contaminated area. This pollutant was rapidly increased due to uncontrolled emission of mercury from power plan, gold mining process and from other sources. The one possible and reasonable method in mercury bioremediation is by using genetically modified plant expressing bacterial-mercury resistance gene. Group of Mer gene was characterized encode mercury transporter and mercury detoxification protein in bacteria. On this study, Blast search on database based on known Mer protein sequence, it shows that these proteins were conserved among bacteria. These groups of genes are potentially to be cloned and transformed into plant for phytoremediation purposes. In order to enhance mercury uptake and reduce its toxicity, multiple genes transformation are considered to be effective approach for transgenic plant construction. This transgenic plant should survive in medium with high concentration of mercury and it should have activities in mercury uptake, detoxification, and Volatilization.